Resolution of vascular inflammation in patients with new-onset giant cell arteritis: data from the RIGA study. (8th April 2021) - Schönau, Verena; Roth, Jessica; Tascilar, Koray; Corte, Giulia; Manger, Bernhard; Rech, Juergen; Schmidt, Daniela; Cavallaro, Alexander; Uder, Michael; Crescentini, Filippo; Boiardi, Luigi; Casali, Massimiliano; et al.
Abstract: Objectives: Efficacy evaluation of GCA treatment is primarily based on non-specific symptoms and laboratory markers. We aimed to assess the change in vascular inflammation in patients with large vessel (LV)-GCA under different treatments using [18F]FDG PET/CT. Methods: Observational study on patients with new-onset, active LV-GCA starting treatment with either prednisolone monotherapy (PRED) or combination with MTX or tocilizumab (TOC). All patients underwent baseline and follow-up PET/CT. The aorta and its major branches were assessed using PET vascular activity score (PETVAS) by independent readers. Cumulative glucocorticoid doses and cessation of glucocorticoid treatment were documented in all patients. Results: We included 88 LV-GCA patients, 27 were treated with PRED, 42 with MTX and 19 with TOC. PETVAS decreased from 18.9–8.0 units at follow-up in the overall population ( P <0.001). PETVAS changes were numerically higher in patients receiving MTX (−12.3 units) or TOC (−11.7 units) compared with PRED (−8.7). Mean cumulative prednisolone dosages were 5637, 4418 and 2984 mg in patients treated with PRED, MTX and TOC ( P =0.002). Risk ratios for glucocorticoid discontinuation at the time of follow-up PET/CT were 6.77 (95% CI: 1.01, 45.29; P =0.049) and 16.25 (95% CI: 2.60, 101.73; P =0.003) for MTX and TOC users compared with PRED users. Conclusion: Treatment of LV-GCA inhibits vascular inflammation in the aorta and its major branches. While similar control of vascular inflammation was achieved with PRED, MTX and TOC treatments, TOC showed a strong glucocorticoid sparing effect, supporting the concept of initial combination therapy.